Síntese de pseudo-peptídeos contendo calcogenonucleosídeos via reações de UGI como potenciais inibidores do SARS-CoV-2 - Rosa, Raquel Mello da (2023)
In this work, a reaction protocol was developed for a new class of pseudo-peptides through multicomponent reactions (MCR) of the Ugi’s four component reaction (U-4CR) type, starting from chalcogenonucleosides. The synthetic route was planned to have a single reaction step under mild conditions. The U-4CR reactions provide great structural versatility since the four components presented groups that could be modified: amine, aldehyde, carboxylic acid, and isocyanide. This study emphasized the amine component, in which 5'-arylchalcogenyl-3-amino-thymidines 5a-f were employed. The carboxylic acid component was also explored, two types of isocyanates were studied, and only one aldehyde was used in the reactions. The synthetic route involved a one-pot reaction at room temperature using an ethanolic milieu, and the 9a-q products were obtained with yields ranging from 25 to 77%. The products were characterized by 1H and 13C NMR spectroscopy, and also HRMS. Two-dimensional 1H and 13C NMR experiments were carried out, however, the registered spectra exhibited poor resolution and no signal attribution was performed. In silico molecular docking studies were performed to evaluate the possible interactions between the obtained compounds and the main protease (Mpro) of SARS-CoV-2. The seventeen compounds were evaluated, and nine compounds exhibited favorable interactions at the stable position close to the active site of the Mpro of SARS-CoV-2, with a highlight for compounds 9b and 9h, whose binding energies with Mpro are -8.7 and -8.8 kcal mol-1, respectively, which are bigger than the exhibit by the standard drug nirmatrelvir. In concluding remarks, seventeen new molecules were synthesized in good yields, making clear the success of Ugi 4-CR reactions in forming pseudo-peptides using chalcogenonucleosides. As prospects for further studies, these molecules can be important targets for investigating biological activities, such as evaluating antitumor activity, among others.